DAMPAK VARIABEL KEUANGAN TERHADAP PENCAPAIAN KEUNTUNGAN PERUSAHAAN KELOMPOK INDUSTRI KONSTRUKSI DI BURSA EFEK JAKARTA - Akhmad Sodikin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This study aims to determine the effect of financial variables, namely the current ratio and debt to equity ratio of companies in the construction industry group listed on the Indonesia stock exchange either partially or simultaneously. The data used includes construction industry group companies. Data were analyzed using regression analysis using the F-test and t test. Based on the results of the analysis it is known that the current ratio variables and the debt to equity ratio affect the return on equity variable in the construction industry stocks on the Indonesia stock exchange. Partially the current variable and debt to equity ratio also partially influence.